Pembatalan Akta Pembiayaan Mudharabah yang Tidak Berdasarkan Prinsip Syariah - Anggita, Sheila Novia; Susanti, Dyah Ochtorina; Tektona, Rahmadi Indra (Universitas Muhammadiyah Kotabumi, 2024)
The cancellation of a mudharabah financing deed that does not comply with sharia principles has major legal repercussions, such as cancellation of contracts and restitution of rights obtained by both parties. The Bank may be required to refund any payments or profits made from unauthorized transactions. Notary / PPAT plays a role in ensuring compliance with sharia principles and fair settlement. Suggestions for banks include improved vetting, staff training, information transparency, and ensuring compliance with sharia law. The debtor needs to understand the principles of sharia and abide by the agreement. Notaries must conduct careful document checks, consultation with sharia experts, and constant education on sharia principles. Thus, collaboration between banks, debtors, and notaries/PPAT is important to ensure compliance with sharia principles and fair settlement in such cases. Keywords: mudharabah, Shariah principles, Notary/PPAT